(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The present study is focus on “A Geographical Analysis of Tahsil wise area under Irrigation Facility in Solapur District (MS)”. There are six 11 Solapur District. Thus, the present study is entirely based on the secondary data